Research title: Creating a break between births (family planning) from the perspective of Islam and medicine: - Saiqal, Oniba; Aram, Fahima (Eximia, 2023)
Prevention of pregnancy, which is one of the basic components of family planning, which is generally called intentional prevention of pregnancy during sexual intercourse, is done by various methods such as: creating barriers, spices or surgery. The main purpose of these methods is to prevent sperm from reaching the seed through the use of condoms and diaphragms, to prevent spawning and to prevent the induction and implantation of the zygote. Preventing pregnancy in Islam is permissible considering the consent of the couple and the interests of the family. Although their number has increased, the purpose of family planning is to create a gap between births to maintain the mother’s physical ability and to have enough time to raise the previous child, which is legally acceptable and desirable, because according to According to the verse of the Holy Qur’an When the Holy Quran was revealed, they prevented pregnancy and the Messenger of God, peace and blessings of God be upon him, did not forbid them from doing so. Objective: To know the rules of family planning from the perspective of Islamic law and its value in medicine. Research question: What is the value and importance of spacing births in Islam and medicine? Research method: It is a library that is taken from reliable sources such as the Holy Quran, hadiths, authoritative jurisprudential books and authoritative medical journals. Final result: Family planning is to create a gap between births to maintain the physical ability of the mother and have enough time to raise the previous child; That this practice is not prohibited from the religious point of view, the authentic books of hadiths, including Sahih al-Bukhari, have made two chapters of it expulsion, and Sahih Muslim, one chapter has been made special to prevent having children under the title of chapters of the decree of expulsion.